Synergistic resin anchoring technology of rebar bolts in coal mine roadways. (March 2022) - Wang, Wei; Pan, Yishan; Xiao, Yonghui
Abstract: The resin anchoring process is a critical aspect of coal mine roadway support, but presently faces several serious challenges. For example, resin s cannot be properly broken and mixed, often leak, and their density and circumferential thickness values frequently deviate from the design values. This results in a reduced effective anchorage length and prevents the correct application of a high pretension force. To address these issues, this study presents a systematic analysis of the anchoring characteristics of roadway bolts including theoretical calculations, a detailed analysis on the influence of mixing density, mixing parameters, and pretension force on the anchoring performance, and a primary focus on the components and mechanism within synergistic anchoring technology. Numerical simulations are performed following the orthogonal experiment method to optimize and determine the synergistic component structural parameters, and laboratory tests are conducted to compare and analyze the modes of the combined synergistic component use. The working performance of the synergistic anchoring technology is comprehensively verified using field tests. The results show that the anchoring system's bearing strength, yield displacement, bearing time, and energy absorption capacity are greatly improved when using a combination of the synergistic components. Bolts applied in the field using the proposed synergistic anchoring technology produce significantly higher anchoring force and pretension moment values than ordinary bolts, exceed the engineering requirements, and produce a good overall anchoring effect. A high pretension force can be applied to enhance the support capacity, ensure the bolt resin anchor quality for coal mine roadways, and improve the roadway bearing capacity under static and dynamic loading, which have high practical significance and application value. Highlights: Coal mine roadway rebar bolt anchoring problems and features are analyzed in detail. A synergistic bolt anchoring component is developed. Synergistic anchoring technology is systematically proposed. A combination of synergistic components improves the anchor support properties. The performance parameter exceeds the requirements with higher support capacity.